Синхронно-асинхронні турбогенератори в структурі генеруючих потужностей енергосистем. Наукові основи створення та їхня експлуатація - Титко, О.І.; Васьковський, Ю.М. (Технічна електродинаміка, 2012)
Advantages to a power supply system of use of synchronous-asynchronous structure of generating capacities are considered. For this purpose the universal type of synchronous-asynchronous turbogenerators is offered on the basis of use external buffer systems. Research of processes and a scientific substantiation of new ways of making of problem units for such machines is resulted.